2016
DOI: 10.1080/13691058.2016.1144791
|View full text |Cite
|
Sign up to set email alerts
|

‘Struggling to be the alpha’: sources of tension and intimate partner violence in same-sex relationships between men

Abstract: In countries such as the USA, gay and bisexual men experience high rates of intimate partner violence. However, little is known about the factors that contribute to this form of violence. In this study, we examine gay and bisexual men’s perceptions of sources of tension in same-sex male relationships and how these may contribute to intimate partner violence. We conducted seven focus group discussions with 64 gay and bisexual men in Atlanta, GA. Focus groups examined men’s reactions to the short-form revised Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 41 publications
(43 reference statements)
1
27
0
3
Order By: Relevance
“…The stress created by this internalized stigma, coupled with other behaviors such as drug and alcohol use (which may also be exacerbated by minority stress factors), may have significant effects on IPV risk. Factors associated with minority stress and dyadic power struggles were among precipitants of IPV in a recent qualitative study of male couples ( Goldenberg et al, 2016 ). Findings revealed that IPV was more common among partners who had experienced homophobic violence and who had traditionally hegemonic views of masculinity that they had difficulty negotiating, referred to as “struggling to be the alpha” ( Goldenberg et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The stress created by this internalized stigma, coupled with other behaviors such as drug and alcohol use (which may also be exacerbated by minority stress factors), may have significant effects on IPV risk. Factors associated with minority stress and dyadic power struggles were among precipitants of IPV in a recent qualitative study of male couples ( Goldenberg et al, 2016 ). Findings revealed that IPV was more common among partners who had experienced homophobic violence and who had traditionally hegemonic views of masculinity that they had difficulty negotiating, referred to as “struggling to be the alpha” ( Goldenberg et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent research among this group, age has been reported to be a significant factor in IPV—with violence decreasing with age and having an older partner reducing the risk of experiencing violence ( Stephenson et al, 2013 ). It has been suggested that for male–male couples, age differences may influence IPV through an older partner’s assertions of dominance and control over the younger partner ( Goldenberg, Stephenson, Freeland, Finneran, & Hadley, 2016 ). Financial stress, depression, and alcohol and drug use in relationships are also correlates of IPV for both heterosexual couples and same-sex male and female couples ( Carvalho et al, 2011 ; Goldenberg et al, 2016 ; Leone, Crane, Parrott, & Eckhardt, 2016 ; Stall et al, 2003 ; Stephenson, Rentsch et al, 2011 ; Stephenson et al, 2013 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations